Host-Adaptive Divergence Shapes the Genetic Architecture of Magnaporthe oryzae in Southern China’s Rice Agroecosystems - Xin Liu; Jun Fu; Zhao Deng; Xinwei Chen; Xiaochun Hu; Zhouyi Tu; Qiuyi Wang; Yuxuan Zhu; Pengcheng Chen; Zhenan Bai; Tiangang Liu; Xuanwen Zhang; et al. (Journal of Fungi)
Rice blast disease, caused by the ascomycete fungus Magnaporthe oryzae (syn. Pyricularia oryzae), poses a severe threat to global rice production. Southern China, a major rice-growing region characterized by diverse agroecological conditions, faces substantial challenges from blast disease, yet our understanding of the genetic structure of M. oryzae populations in this region remains limited. Here, we analyzed 885 M. oryzae strains from 18 nurseries across four rice ecological regions in Southern China using a panel of genome-wide SNP markers. Phylogenetic and principal component analyses revealed three distinct clonal lineages: lineage I (58.19%), lineage II (21.36%), and lineage III (20.45%). Lineage I exhibited a broader geographic distribution compared to the other two lineages. Host-adapted divergence was observed across rice subspecies, with lineage III predominantly associated with japonica growing-regions, while lineages I and II mainly colonized indica rice-growing regions. Genetic diversity exhibited significant spatial heterogeneity, with the nucleotide diversity (π) ranging from 0.17 in South China to 0.32 in the Middle–Lower Yangtze River region, reflecting differential cropping systems. The predominantly negative Tajima’s D values across populations suggested recent expansion or selective sweeps, likely driven by host resistance pressures. High genetic differentiation between lineage I and other lineages contrasted with low divergence between lineages II and III, indicating distinct evolutionary trajectories. Furthermore, an uneven distribution of mating types among three genetic lineages was observed, suggesting limited sexual recombination within clonal lineages. The information obtained in this study may be beneficial in devising suitable strategies to control rice blast disease in Southern China.